Investment in Education: Do Economic Volatility and Credit Constraints Matter? - Karnit Flug; Antonio Spilimbergo; Erik Wachtenheim (Inter-American Development Bank, Office of the Chief Economist, 1999)
The focus of this paper is the link between income volatility and the accumulation of human capital in the presence of credit constraints. Also, the effect of income inequality on the accumulation of human capital within the same framework is studied.
Keywords: 330